1974
DOI: 10.1093/bja/46.7.514
|View full text |Cite
|
Sign up to set email alerts
|

Studies of Drugs Given Before Anaesthesia Xxiv: Metoclopramide With Morphine and Pethidine

Abstract: When given with pethidine 100 mg or morphine 10 mg as preanaesthetic medication, 10 and 20 mg of metoclopramide cause a reduction in postoperative nausea and vomiting in women undergoing a standard operation with a standard anaesthetic technique. The preoperative emetic effects of pethidine are almost completely abolished by metoclopramide. An additional 10-20 mg of metoclopramide, given i.m. at the end of the operation markedly reduces the emetic effects of pethidine premedication but has less effect when mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1975
1975
2009
2009

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(7 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…When used in low doses (10 mg), as for PONV, metoclopramide has few side effects. High doses can cause extrapyramidal symptoms [97,98].…”
Section: Benzamidesmentioning
confidence: 99%
See 1 more Smart Citation
“…When used in low doses (10 mg), as for PONV, metoclopramide has few side effects. High doses can cause extrapyramidal symptoms [97,98].…”
Section: Benzamidesmentioning
confidence: 99%
“…The antiemetic efficacy of metoclopramide has been controversial due to different dosing, timing and types of surgery and anesthesia techniques studied. Antiemetic effectiveness has been reported for the control of PONV in the immediate postoperative period when metoclopramide's prokinetic gastric effects increase lower esophageal sphincter tone and gastric motility and counteract the delayed gastric emptying effects of opioids [95,98]. Because of its short duration of action (1-2 h), low doses of metoclopramide such as 10 mg does not appear to be as effective for PONV prevention when administered prior to the start of anesthesia.…”
Section: Benzamidesmentioning
confidence: 99%
“…Although previous studies (32)(33)(34)(35)(36) have demonstrated the efficacy of metoclopramide in controlling cancer-associated gastrointestinal symptoms, its short eliminate half-life necessitates frequent administration in order to provide continuous relief of chronic symptoms. The short duration of action of metoclopramide in clinical trials of postoperative nausea and vomiting (43)(44)(45) supports the view that sustained plasma metoclopramide concentrations will be required to suppress nausea, vomiting, and possibly other gastrointestinal symptoms associated with chronic conditions such as cancer. The need for frequent administration of continuous infusion in order to maintain plasma metoclopramide concentrations may be impossible to manage for those patients cared for in the community.…”
Section: Discussionmentioning
confidence: 81%
“…(1) However, metoclopramide manages nausea and vomiting efficiently when induced by paralytic ileum, due to high morphine does for control of postoperative pain. (46) Rescue treatment For rescue treatment, blockers of the 5-HT3 receptors have been the most studied drugs. This class presents better results when treating vomiting than nausea episodes.…”
Section: Preoperative Strategiesmentioning
confidence: 99%